2015
DOI: 10.1038/ncomms7414
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies a new susceptibility locus for cleft lip with or without a cleft palate

Abstract: Nonsyndromic cleft lip with or without a cleft palate (NSCL/P) is among the most common human congenital birth defects and imposes a substantial physical and financial burden on affected individuals. Here, we conduct a case-control-based GWAS followed by two rounds of replication; we include six independent cohorts from China to elucidate the genetic architecture of NSCL/P in Chinese populations. Using this combined analysis, we identify a new locus at 16p13.3 associated with NSCL/P: rs8049367 between CREBBP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
190
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(205 citation statements)
references
References 38 publications
12
190
3
Order By: Relevance
“…Recent studies have reported association of nsCL/P with many loci throughout the genome [11][12][13][14][39][40][41][42] . Replication of those results on various populations and the investigation of mechanisms by which these variants influence cleft susceptibility are crucial for better understanding of genetic architecture of nsCL/P.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported association of nsCL/P with many loci throughout the genome [11][12][13][14][39][40][41][42] . Replication of those results on various populations and the investigation of mechanisms by which these variants influence cleft susceptibility are crucial for better understanding of genetic architecture of nsCL/P.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of statistical power due to sample size and low MAF of the genotyped SNPs in Africans could also be possible reasons. For example, rs2235371-an SNP of IRF6 that is in high-linkage disequilibrium and the same locus as rs642961 and that has been associated with NSCL/P among mostly Asians (Sun et al 2015) and in some Europeans (Zucchero et al 2004)-does not exist in the African population (http://browser.1000genomes.org/index.html). It is also possible that even when no associations are detected between reported loci and NSOFCs, potentially pathogenic variants may be observed in NSOFC cases.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis revealed additional NSCL/P susceptibility loci: THADA, SPRY2, 15q22.2 (TPM1), and 1p36 (PAX7; Ludwig et al 2012). Recently, a GWAS involving Asians implicated 16p13.3 (ADCY9; Sun et al 2015) in the etiology of NSCL/P, whereas a GWAS involving dogs and a Guatemalan population gave a suggestive association for ADAMTS20 (Wolf et al 2015).…”
Section: Research-article2016mentioning
confidence: 99%
“…On the other hand, we diminish the relevance of IRF6 SNP rs642961 in susceptibility to NSCL/P in our population. Our results are consistent with recent findings that suggest that the association observed for IRF6 may be driven by other variants (Sun et al, 2015), even though a functional role has been attributed to this variant . Finally, we also reported, for the first time in our population, the association of a marker in 20q12 region.…”
Section: General Discussion and Conclusionsupporting
confidence: 83%
“…Moreover, it confirmed the 8q24 locus as the strongest association in NSCL/P (Box 1). Recently, (Sun et al, 2015) conducted the fifth GWAS on NSCL/P, the first on a totally non-European sample (the Chinese population). A new susceptibility locus was revealed in this study (16p13), reinforcing the importance of testing populations other than Europeans.…”
Section: Gwas and The Common Susceptibility Variantsmentioning
confidence: 99%